2003
DOI: 10.1021/la027020u
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Preparation of Molybdenum Trioxide Thin Films:  Effect of Sintering on Electrochromic and Electroinsertion Properties

Abstract: Molybdenum trioxide (MoO3) thin films prepared by cathodic electrodeposition on indium-tin-oxide coated glass substrates from aqueous peroxo-polymolybdate solutions have been studied as a function of sintering temperature (25-450 °C). Cyclic voltammetry, chronopotentiometry, chronoamperometry, and spectroelectrochemical measurements performed with MoO 3 thin films in 1 M LiClO4/propylene carbonate demonstrate that the electrochemical behavior (Li + insertion/extraction and coloration) is strongly dependent upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
93
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 48 publications
7
93
1
Order By: Relevance
“…The present material has high specific capacities of 252 and 227 mA h g −1 for the initiation of charge-discharge process, respectively. Its capacities were decreased to 158 and 124 mA h g −1 after 30 cycles due to the irreversible capacity associated with the decomposition of the electrolytic solution and the solid-electrolyte interface (SEI) formation [25][26][27]. They were constant at 160 and 119 mA h g −1 afterwards.…”
Section: Resultsmentioning
confidence: 99%
“…The present material has high specific capacities of 252 and 227 mA h g −1 for the initiation of charge-discharge process, respectively. Its capacities were decreased to 158 and 124 mA h g −1 after 30 cycles due to the irreversible capacity associated with the decomposition of the electrolytic solution and the solid-electrolyte interface (SEI) formation [25][26][27]. They were constant at 160 and 119 mA h g −1 afterwards.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of bath formulation and growth conditions on the oxidation state of molybdenum oxide films has been studied in detail in the past [3]. McEvoy and Stevenson described the cathodic electrodeposition of MoO 3 from acidic peroxo-polymolybdate solutions onto indium-doped tin oxide (ITO) electrode [27]. The same authors deeply investigated the mechanism of molybdenum oxides deposition using different tools, namely chronocoulometry and quartz crystal microbalance techniques [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the sweep rate in cyclic voltammetry experiments determined the formation of either α-or -MoO 3 [24]. Remarkably, X-ray diffraction analyses indicate that the films are typically amorphous (or poorly crystalline) in the as-deposited state [11,24,27]. Therefore, annealing at temperatures equal to (or beyond) 250 ºC is typically required to achieve fully crystalline films [11,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method consumes a lot of water and also has very low yield as reported by Mizushima et al [15] that the Mo content in the final solution was reported only 3.3 % of the initial value. Some research groups tried to synthesize b-MoO 3 from other molybdenum sources, such as peroxo-polymolybdate [16], commercial a-MoO 3 [17] or sodium molybdate solution [18] but these efforts were unsuccessful. The thermodynamically stable a-MoO 3 was usually detected in the final product.…”
Section: Introductionmentioning
confidence: 99%